THE BIG FIVE PERSONALITY TRAITS TERHADAP FINANCIAL LITERACY DAN INVESTOR RISK BEHAVIOR PADA KELOMPOK INVESTOR GENERASI Z - Putri, Safira Ananda; Ferli, Ossi (Ibs Press, 2024)
This research aims to determine the influence of The Big Five Personality Traits on Financial Literacy and Investor Risk Behavior among Generation Z investors. The hypothesis testing in this research utilizes the PLS (Partial Least Square) method using SmartPLS 4.0. Data collection techniques involve using a Google Form questionnaire to gather the required information. The sample in this study consists of 165 Generation Z individuals participating in investments in the Indonesian Capital Market. The analysis results show that the Personality Trait (Neuroticism) has a positive and significant effect on Investor Risk Behavior, and there are 4 Personality Trait indicators that do not have a positive effect on Investor Risk Behavior, namely Agreeableness, Extraversion, Conscientiousness, and Openness to Experience. The Personality Trait (Openness to Experience) has a positive and significant effect on Financial Literacy, and there are 4 Personality Trait indicators that do not have a positive effect on Financial Literacy, namely Agreeableness, Neuroticism, Conscientiousness, and Extraversion. Financial Literacy has a positive effect on Investor Risk Behavior. Higher education can play an important role in improving financial and investment literacy among Generation Z.